1987
DOI: 10.1007/bf00376346
|View full text |Cite
|
Sign up to set email alerts
|

Lineage analysis of transplanted individual cells in embryos of Drosophila melanogaster

Abstract: We describe the results of cell transplantation experiments performed to investigate mesodermal lineages in Drosophila melanogaster, particularly the lineages of the somatic muscles, the visceral muscles and the fat body. Cells to be transplanted were labelled by injecting a mixture of horseradish peroxidase (HRP) and fluorescein-dextran (FITC) in wild-type embryos at the syncytial blastoderm stage. For transplantation cells were removed from the ventral furrow, 8-12 min after the start of gastrulation, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This suggests that, at least within each parasegment, there are no apparent compartmental restrictions. Similar results have also been obtained by lineage analyses of the mesoderm (Lawrence and Johnston 1982;Beer et al 1987). In addition, the behavior of these cells shows that founder cells of two different types of muscles (in this case, 25 and 5) can be clonally related.…”
Section: Genes and Development 2105supporting
confidence: 70%
See 1 more Smart Citation
“…This suggests that, at least within each parasegment, there are no apparent compartmental restrictions. Similar results have also been obtained by lineage analyses of the mesoderm (Lawrence and Johnston 1982;Beer et al 1987). In addition, the behavior of these cells shows that founder cells of two different types of muscles (in this case, 25 and 5) can be clonally related.…”
Section: Genes and Development 2105supporting
confidence: 70%
“…We do not know at what stage of embryonic development mesodermal cells become committed to particular muscular fates. In transplantation experiments, Beer et al (1987) found that shortly after their invagination, mesodermal cells are not yet committed to form particular muscles or even particular mesodermal tissues. The expression of S59 in several defined mesodermal cells ~2 hr later suggests that at least some mesodermal cells are singled out and assume a specific fate in the late phase of their proliferation or shortly thereafter.…”
Section: Genes and Development 2105mentioning
confidence: 99%
“…The early Drosophila mesoderm is composed of a field of pluripotent cells (Beer et al 1987;Farrell and Keshishian 1999), expressing the TF Twist (Leptin 1991;Baylies and Bate 1996). After gastrulation, these cells dissociate from each other, proliferate, and migrate dorsally, while remaining unspecified.…”
mentioning
confidence: 99%
“…Mesoderm cells undergo up to three post-blastoderm mitoses within 4 h of cellular blastoderm, before mid stage 11 of embryogenesis, in which most of the the embryos examined here were found ( Fig. 3; Hartenstein and Campos-Ortega 1985;Beer et al 1987;Bate 1993). At late cellular blastoderm stage, when the heat shocks were performed, all cells are temporarily arrested in G2.…”
Section: Generation Of Mesodermal Clones and The Timin Of Recombinatimentioning
confidence: 92%